2016
DOI: 10.1111/adb.12425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naltrexone on alcohol self‐administration and craving: meta‐analysis of human laboratory studies

Abstract: Randomized clinical trials have established the efficacy of naltrexone for reducing quantity of alcohol consumption and incidence of relapse to heavy drinking. To evaluate putative treatment mechanisms, human laboratory studies have examined naltrexone's effects on alcohol responses and self‐administration during short‐term medication protocols. Results from these studies are inconsistent and have yet to be examined in aggregate. This meta‐analysis aimed to quantify naltrexone's effects on alcohol self‐adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 55 publications
3
49
0
Order By: Relevance
“…The beta‐endorphin response to alcohol is heritable (Froehlich et al., ) and the response is greater in individuals with a family history of alcoholism than it is in individuals without a family history of alcoholism (Gianoulakis et al., ). Both NTX and VAR reduce alcohol‐induced feelings of intoxication and well‐being and reduce alcohol drinking (Chick et al., ; Childs et al., ; Froehlich et al., ; Hendershot et al., ; Litten et al., ; McKee et al., ; O'Malley and Froehlich, ; Verplaetse et al., ; Volpicelli et al., ). NTX is more effective in decreasing alcohol drinking in individuals with a family history of alcoholism (“family history positive” or “high risk”) than in individuals without a family history of alcoholism (Krishnan‐Sarin et al., ; Monterosso et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beta‐endorphin response to alcohol is heritable (Froehlich et al., ) and the response is greater in individuals with a family history of alcoholism than it is in individuals without a family history of alcoholism (Gianoulakis et al., ). Both NTX and VAR reduce alcohol‐induced feelings of intoxication and well‐being and reduce alcohol drinking (Chick et al., ; Childs et al., ; Froehlich et al., ; Hendershot et al., ; Litten et al., ; McKee et al., ; O'Malley and Froehlich, ; Verplaetse et al., ; Volpicelli et al., ). NTX is more effective in decreasing alcohol drinking in individuals with a family history of alcoholism (“family history positive” or “high risk”) than in individuals without a family history of alcoholism (Krishnan‐Sarin et al., ; Monterosso et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…NTX decreases alcohol drinking in rodents in a variety of situations including during unrestricted access to alcohol, during restricted or scheduled access to alcohol, and during reinstatement of access to alcohol following alcohol deprivation. In humans, NTX decreases heavy drinking in both alcohol‐dependent and nondependent alcohol drinkers (for review, see Chick et al., ; Hendershot et al., ). NTX also reduces alcohol craving in individuals with AUD (Volpicelli et al., ) and reduces alcohol drinking in young adults (O'Malley et al., ).…”
mentioning
confidence: 99%
“…Some treatments in clinical use, such as nalmefene or naltrexone, target μ-opiate receptors and reduce volumes of alcohol drunk thereby reducing harm, or relapse rates in some individuals addicted to alcohol, respectively (Vendruscolo et al, 2012;Vengeliene et al, 2009;Vengeliene et al, 2014). However, while clinically significant these treatments are not optimal (Franck and Jayaram-Lindström, 2013;Hendershot et al, 2016;Rösner et al, 2010). Opioid receptor-mediated mechanisms have been shown to reduce alcohol drinking, craving for alcohol and established CS-controlled alcohol seeking (Vengeliene et al, 2008); moreover μ-opioid receptors in the prefrontal context have been implicated in compulsive eating (Blasio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Opioid antagonist drugs such as naltrexone are used as pharmacotherapy to reduce symptoms of craving (excessive 'wanting') across both drug-and behavioral addictions (Lobmaier, Kunøe, Gossop, & Waal, 2011). A recent meta-analysis of randomized clinical trials on naltrexone treatment of alcohol dependence showed overall reduced craving for, and self-administration of, alcohol during naltrexone treatment (Hendershot, Wardell, Samokhvalov, & Rehm, 2016). Reduced craving following MOR antagonism with naltrexone has also been shown for heroin- (Sullivan, Vosburg, & Comer, 2006), nicotine- (King & Meyer, 2000) and amphetamine dependent patients (Nitya Jayaram-Lindstrom et al, 2007).…”
Section: Direct µ-Opioid Modulation Of Reward Motivation?mentioning
confidence: 99%
“…Second, while a prevalent view of the role of MOR in reward is that it is involved in the consummatory 'liking' aspects of reward, it is clear that MOR has independent influence on anticipatory 'wanting' behaviors as well (Chelnokova et al, 2014;Hendershot et al, 2016;Peciña & Berridge, 2013 As such, the principal goal of this thesis was to ensure that any potential drug effects observed in the fMRI reward tasks were not due to confounds such as CO2-related BOLD changes, slowed motor coordination, or drug effects on mood, nausea, hunger, sedation, and general drug experience. In addition to these primary aims, preliminary results of drug effects in the Food Wanting and Regulation task will also be presented and discussed briefly.…”
Section: Study Rationalementioning
confidence: 99%